1994
DOI: 10.1063/1.467975
|View full text |Cite
|
Sign up to set email alerts
|

Infrared laser-induced photofragmentation of the positive and negative ions of size-selected SF6 (NO)n clusters

Abstract: A detailed study has been undertaken on the infrared photofragmentation of SF 6 (NO); cluster ions. A line-tuneable CO 2 laser has been used to excite the J)3 vibrational mode of the SF 6 molecule which is followed by the observation of three separate fragmentation channels: -SF(j, -NO, and -2NO. The relative intensities of the fragments are found to be sensitive to the sign of the charge on the ion, the cluster size, and whether n is either odd or even. Within clusters of the same charge, the most marked tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
(3 reference statements)
0
30
0
Order By: Relevance
“…6 MIKE ͑Mass-analyzed ion kinetic energy͒ spectra were recorded for each of the ions under conditions where both unimolecular and collisioninduced fragmentation patterns could be identified separately. For the clusters NO ϩ •͑H 2 O͒ 3-5 and NO 2 ϩ •͑H 2 O͒ 2-4 , the parent signals were reduced by approximately one-half through the introduction of collision gas ͑air at ϳ10 Ϫ6 mbar) into a cell located in the second field-free region between the magnet and the electrostatic analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…6 MIKE ͑Mass-analyzed ion kinetic energy͒ spectra were recorded for each of the ions under conditions where both unimolecular and collisioninduced fragmentation patterns could be identified separately. For the clusters NO ϩ •͑H 2 O͒ 3-5 and NO 2 ϩ •͑H 2 O͒ 2-4 , the parent signals were reduced by approximately one-half through the introduction of collision gas ͑air at ϳ10 Ϫ6 mbar) into a cell located in the second field-free region between the magnet and the electrostatic analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…A disadvantage is that the technique is currently restricted to ligands that are volatile; however, some success has been obtained with a dual pick-up system where involatile ligands are held in a heated reservoir inside the vacuum chamber that houses the nozzle. 1 Previous experimental work has demonstrated that the use of argon as opposed, for example, to helium is crucial to the success of the pick-up technique [33], and separate molecular dynamics simulations have shown that cooling through argon atom evaporation is an integral part of the pick-up mechanism [34].…”
Section: Pick-up Process and Ionizationmentioning
confidence: 99%
“…In a series of recent papers [15][16][17][18] we have shown that, through the careful selection of cluster/chromophore combinations, it is possible to study the laser-induced infrared photofragmentation spectroscopy of single neutral molecules in association with mass-selected cluster ions. A necessary condition for the success of such experiments is that, for a chromophore Y and a cluster X n , the relative ionization energies ͑IE͒ are such that IE(Y )ϾIE(X n ).…”
Section: Introductionmentioning
confidence: 99%
“…A necessary condition for the success of such experiments is that, for a chromophore Y and a cluster X n , the relative ionization energies ͑IE͒ are such that IE(Y )ϾIE(X n ). [15][16][17][18] Under these circumstance, the cluster can be ionised in the knowledge that it is X n which carries the positive charge and, therefore, allows ions to be mass selected. However, through a suitable selection of chromophores, spectroscopic studies can be undertaken on a single molecule of Y that is cluster-bound and which, at the same time, has a gas-phase infrared spectrum that is well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation